Investigate Instability Behaviour In High Power LDMOS Power Amplifier - Ab Rahman, Ida Idyuni (Universiti Sains Malaysia, 2005)
In this thesis the models of LDMOS power amplifier was been investigated using Advanced Design System (ADS) version 2004A software from Agilent Technologies for operation below 1 GHz frequency range. There are two models considered in this project. Both of the models were provided by Motorola. The two models are RD01MUS1 and RD07MVS1 based on a 59 mil LDMOS transistor using type of FR4 PCB Board. Large-signal simulations of both models have demonstrated results, which lead to the conclusion that, these models cannot be efficiently utilised for design of input and output matching networks using Unilateral value for Conjugate Matching. However, there are other matching applications; Load Line Matching and Load Pull Analysis that can be used that have not been explored yet by the researcher due to time constraint. Hence, it is important to take into account during new processes of LDMOS as well as to improve the CAD model. The final conclusion regarding LDMOS cannot be made just based on these simulation results, since they are not in accordance with the published ones. The next step should be aimed at improving the model and further investigation of LDMOS to prove their ability to operate with optimum efficiency in above1 GHz frequency range.